2019
DOI: 10.1002/iid3.273
|View full text |Cite
|
Sign up to set email alerts
|

The use of amino acid‐based nutritional feeds is effective in the dietary management of pediatric eosinophilic oesophagitis

Abstract: Introduction Eosinophilic oesophagitis (EoE) is an immune‐mediated, chronic disease characterized by eosinophilic inflammation and esophageal dysfunction. Specific food allergens including cow's milk protein, are partially causative to disease progression, and dietary management forms three main options; the elemental diet (ED), the empirical elimination diet (EED), and the targeted elimination diet (TED). The dietary choice should be individualized, however, the European Society for Pediatric Gastroenterology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
(269 reference statements)
0
7
0
Order By: Relevance
“…In conclusion, the ELED is highly effective in the management of pediatric EoE, but should rather be used in formula fed infants or as a final rescue therapy for older children who did not experience histological remission on other dietary therapies ( 7 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the ELED is highly effective in the management of pediatric EoE, but should rather be used in formula fed infants or as a final rescue therapy for older children who did not experience histological remission on other dietary therapies ( 7 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exact prevalence of EoE in both breast-and formula-fed infants [61] is difficult to determine because few infants have endoscopy and esophageal biopsies before been attempted CM free diet or PPI treatment. Moreover, pediatric EoE case series did not provide a subgroup analysis of infants [89] and one large report on infant esophagitis did not detail eosinophilic infiltration [56]. Noteworthy, several early-life factors, including maternal fever, preterm labor, cesarean delivery, esophageal atresia, antibiotic or acid suppressant use in the first months of life, dysbiosis, other atopic conditions and celiac disease have been associated with risk of pediatric EoE [90,91].…”
Section: The Third Wheel: Eosinophilic Esophagitismentioning
confidence: 99%
“…On the contrary, in infants the first and, in almost all cases, the only treatment needed for EoE is CM free diet with recommended amino acid formula [31,86,87]. In a recent review of ten studies, enrolling 462 EoE patients (mean age 6.7 years, range, 4 months-20 years), elemental diet resulted in clinical and histological remission (defined as ≤10 eosinophils/hpf) in 75-100% of children [89]. Despite diagnostic difficulties an early recognition of EoE is important to resolve or reduce clinical manifestations and possible long term esophageal complications.…”
Section: The Third Wheel: Eosinophilic Esophagitismentioning
confidence: 99%
“…A review showed that the use of AAF diminished eosinophil count, inducing remission in 75%-100% of children. Based on these data, AAF is considered superior compared with the food elimination diet (FED) [103][104][105]. However, an elemental diet with AAF is used only to treat persistent active EoE, refractory to other conventional drugs and/or empiric diets because of poor palatability, use of nasogastric tubes, lack of adherence, psychological impact, and high costs [103][104][105].…”
Section: Diet Management Of Eosinophilic Esophagitismentioning
confidence: 99%